5.21.3 Problems 201 to 300

Table 5.989: Higher order, Linear, Homogeneous and constant coefficients

#

ODE

Mathematica

Maple

5930

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+12 y^{\prime }-8 y = 0 \]

5932

\[ {}y^{\prime \prime \prime \prime }+3 y^{\prime \prime \prime } = 0 \]

5933

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime } = 0 \]

5934

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }-11 y^{\prime \prime }-12 y^{\prime }+36 y = 0 \]

5935

\[ {}36 y^{\prime \prime \prime \prime }-37 y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

5936

\[ {}y^{\prime \prime \prime \prime }-8 y^{\prime \prime }+36 y = 0 \]

5939

\[ {}y^{\prime \prime \prime \prime }+5 y^{\prime \prime }+6 y = 0 \]

5941

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime }+4 y = 0 \]

5942

\[ {}y^{\prime \prime \prime }+8 y = 0 \]

5943

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime } = 0 \]

5944

\[ {}y^{\left (5\right )}+2 y^{\prime \prime \prime }+y^{\prime } = 0 \]

5949

\[ {}3 y^{\prime \prime \prime }+5 y^{\prime \prime }+y^{\prime }-y = 0 \]

6147

\[ {}y^{\prime \prime \prime }+y = 0 \]

6148

\[ {}y^{\prime \prime \prime }+y^{\prime \prime }-6 y^{\prime } = 0 \]

6149

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }-9 y^{\prime }-5 y = 0 \]

6150

\[ {}y^{\prime \prime \prime \prime }+4 y = 0 \]

6210

\[ {}y^{\prime \prime \prime }+2 y^{\prime \prime }+2 y^{\prime } = 0 \]

6229

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }+13 y^{\prime \prime }-18 y^{\prime }+36 y = 0 \]

6389

\[ {}x^{\prime \prime \prime }-x^{\prime \prime }+x^{\prime }-x = 0 \]

6391

\[ {}x^{\prime \prime \prime \prime }+x = 0 \]

6392

\[ {}x^{\prime \prime \prime }-3 x^{\prime \prime }-9 x^{\prime }-5 x = 0 \]

6555

\[ {}y^{\prime \prime \prime \prime }-y = 0 \]

6692

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+12 y^{\prime }-8 y = 0 \]

6702

\[ {}y^{\prime \prime \prime }+y^{\prime \prime }-2 y^{\prime } = 0 \]

6704

\[ {}y^{\prime \prime \prime \prime }-6 y^{\prime \prime \prime }+12 y^{\prime \prime }-8 y^{\prime } = 0 \]

6707

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+9 y^{\prime }-9 y = 0 \]

6708

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime } = 0 \]

6709

\[ {}y^{\prime \prime \prime \prime }-6 y^{\prime \prime \prime }+13 y^{\prime \prime }-12 y^{\prime }+4 y = 0 \]

6710

\[ {}y^{\left (6\right )}+9 y^{\prime \prime \prime \prime }+24 y^{\prime \prime }+16 y = 0 \]

6931

\[ {}y^{\prime \prime \prime \prime }-20 y^{\prime \prime \prime }+158 y^{\prime \prime }-580 y^{\prime }+841 y = 0 \]

7554

\[ {}a^{2} y^{\prime \prime \prime \prime } = y^{\prime \prime } \]

7640

\[ {}y^{\prime \prime \prime }-8 y = 0 \]

7641

\[ {}y^{\prime \prime \prime \prime }+16 y = 0 \]

7642

\[ {}y^{\prime \prime \prime }-5 y^{\prime \prime }+6 y^{\prime } = 0 \]

7643

\[ {}y^{\prime \prime \prime }-i y^{\prime \prime }+4 y^{\prime }-4 i y = 0 \]

7644

\[ {}y^{\prime \prime \prime \prime }+5 y^{\prime \prime }+4 y = 0 \]

7645

\[ {}y^{\prime \prime \prime \prime }-16 y = 0 \]

7646

\[ {}y^{\prime \prime \prime }-3 y^{\prime }-2 y = 0 \]

7647

\[ {}y^{\prime \prime \prime }-3 i y^{\prime \prime }-3 y^{\prime }+i y = 0 \]

7648

\[ {}y^{\prime \prime \prime }-4 y^{\prime } = 0 \]

7649

\[ {}y^{\left (5\right )}-y^{\prime \prime \prime \prime }-y^{\prime }+y = 0 \]

7652

\[ {}y^{\prime \prime \prime \prime }-y = 0 \]

7653

\[ {}y^{\left (5\right )}+2 y = 0 \]

7654

\[ {}y^{\prime \prime \prime \prime }-5 y^{\prime \prime }+4 y = 0 \]

7655

\[ {}y^{\prime \prime \prime }+y = 0 \]

7656

\[ {}y^{\prime \prime \prime }-i y^{\prime \prime }+y^{\prime }-i y = 0 \]

7658

\[ {}y^{\prime \prime \prime \prime }-k^{4} y = 0 \]

7806

\[ {}2 y^{\prime \prime \prime }+y^{\prime \prime }-5 y^{\prime }+2 y = 0 \]

8016

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+2 y^{\prime } = 0 \]

8017

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y^{\prime }-2 y = 0 \]

8018

\[ {}y^{\prime \prime \prime }-y = 0 \]

8019

\[ {}y^{\prime \prime \prime }+y = 0 \]

8020

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }+3 y^{\prime }+y = 0 \]

8021

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime }+6 y^{\prime \prime }+4 y^{\prime }+y = 0 \]

8022

\[ {}y^{\prime \prime \prime \prime }-y = 0 \]

8023

\[ {}y^{\prime \prime \prime \prime }+5 y^{\prime \prime }+4 y = 0 \]

8024

\[ {}y^{\prime \prime \prime \prime }-2 a^{2} y^{\prime \prime }+a^{4} y = 0 \]

8025

\[ {}y^{\prime \prime \prime \prime }+2 a^{2} y^{\prime \prime }+a^{4} y = 0 \]

8026

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+2 y^{\prime \prime }+2 y^{\prime }+y = 0 \]

8027

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }-2 y^{\prime \prime }-6 y^{\prime }+5 y = 0 \]

8028

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = 0 \]

8029

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }-3 y^{\prime \prime }-5 y^{\prime }-2 y = 0 \]

8030

\[ {}y^{\left (5\right )}-6 y^{\prime \prime \prime \prime }-8 y^{\prime \prime \prime }+48 y^{\prime \prime }+16 y^{\prime }-96 y = 0 \]

8031

\[ {}y^{\prime \prime \prime \prime } = 0 \]

11452

\[ {}y^{\prime \prime \prime }-\lambda y = 0 \]

11455

\[ {}y^{\prime \prime \prime }+3 y^{\prime }-4 y = 0 \]

11467

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }-3 y^{\prime }+10 y = 0 \]

11470

\[ {}y^{\prime \prime \prime }+\operatorname {a2} y^{\prime \prime }+\operatorname {a1} y^{\prime }+\operatorname {a0} y = 0 \]

11535

\[ {}y^{\prime \prime \prime \prime } = 0 \]

11537

\[ {}y^{\prime \prime \prime \prime }+\lambda y = 0 \]

11540

\[ {}y^{\prime \prime \prime \prime }+\left (\lambda +1\right ) a^{2} y^{\prime \prime }+\lambda \,a^{4} y = 0 \]

11575

\[ {}f \left (y^{\prime \prime \prime \prime }-2 a^{2} y^{\prime \prime }+a^{4} y\right )+2 \operatorname {df} \left (y^{\prime \prime \prime }-a^{2} y^{\prime }\right ) = 0 \]

11576

\[ {}f y^{\prime \prime \prime \prime } = 0 \]

11584

\[ {}x \left (a y^{\prime }+b y^{\prime \prime }+c y^{\prime \prime \prime }+e y^{\prime \prime \prime \prime }\right ) y = 0 \]

11845

\[ {}2 y^{\prime } y^{\prime \prime \prime }-3 {y^{\prime }}^{2} = 0 \]

12921

\[ {}y^{\prime \prime \prime }-y^{\prime } = 0 \]

12922

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }-y^{\prime }+2 y = 0 \]

12923

\[ {}4 y^{\prime \prime \prime }-3 y^{\prime }+y = 0 \]

12924

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }-y^{\prime }+y = 0 \]

12925

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }-2 y^{\prime }-y = 0 \]

12926

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+9 y^{\prime } = 0 \]

12927

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = 0 \]

12928

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime } = 0 \]

13177

\[ {}x^{\prime \prime \prime }+x^{\prime } = 0 \]

13179

\[ {}x^{\prime \prime \prime }+x^{\prime \prime } = 0 \]

13180

\[ {}x^{\prime \prime \prime }-x^{\prime }-8 x = 0 \]

13182

\[ {}x^{\prime \prime \prime }-8 x = 0 \]

13183

\[ {}x^{\prime \prime \prime }+x^{\prime \prime }-x^{\prime }-4 x = 0 \]

13255

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }-4 y^{\prime }+8 y = 0 \]

13256

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }-4 y^{\prime }+12 y = 0 \]

13397

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+5 y^{\prime }+12 y = 0 \]

13411

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }-y^{\prime }+3 y = 0 \]

13412

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+5 y^{\prime }+12 y = 0 \]

13419

\[ {}y^{\prime \prime \prime }-5 y^{\prime \prime }+7 y^{\prime }-3 y = 0 \]

13420

\[ {}4 y^{\prime \prime \prime }+4 y^{\prime \prime }-7 y^{\prime }+2 y = 0 \]

13421

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+12 y^{\prime }-8 y = 0 \]

13422

\[ {}y^{\prime \prime \prime }+4 y^{\prime \prime }+5 y^{\prime }+6 y = 0 \]

13423

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 0 \]

13424

\[ {}y^{\prime \prime \prime \prime }+8 y^{\prime \prime }+16 y = 0 \]

13425

\[ {}y^{\left (5\right )}-2 y^{\prime \prime \prime \prime }+y^{\prime \prime \prime } = 0 \]